11/#620 Oncologic outcome of patients with stage I immature teratoma treated with surveillance or adjuvant chemotherapy. (4th December 2022) - Marino, Giuseppe; Grassi, Tommaso; Negri, Serena; Testa, Filippo; Ponti, Elena De; Giuliani, Daniela; Marchette, Martina Delle; Sina, Federica; Vicini, Debora; Fumagalli, Diletta; Marchetta, Liliana; Bonazzi, Cristina Maria; et al.
Abstract : Objectives: Immature teratomas (ITs) are a rare disease representing about one-third of all malignant ovarian germ cell tumors. They are frequently diagnosed in young women, and fertility-sparing surgery (FSS) is often the treatment of choice. While stage IA grade 1 ITs do not require adjuvant chemotherapy (CT), its role in other stage I ITs is still controversial. We investigate the impact of surveillance versus adjuvant CT on the recurrence rate in stage I any grade ITs. This is the largest monocentric case series reported to the best of our knowledge. Methods: Clinicopathological data were retrospectively collected from a cohort of patients with stage I ITs treated with FSS in one center between 1980 and 2019. Results: Among the 74 patients included, 9 patients received adjuvant CT while 65 underwent active surveillance. Median follow-up was 188 months. The relapse rate was higher in patients with stage IC (29% vs 10% in stage IA/B) and grade 3 (22% vs 14% and 7% in grade 2 and 1, respectively), while no difference was found between surveillance and adjuvant CT groups (13.9% vs 11.1%) [p = 0, 65]. Both in univariate [OR = 0, 78; CI 95% 0, 09–6, 98 (p = 0, 82)] and multivariate [OR = 0, 25; CI 95% 0, 02–2, 66 (p = 0, 25)] analysis, the post-surgical approach did not influence the recurrence rate. Conclusions: These data support the feasibility of surveillance in stage I immature teratomas. However, the clinician must be aware of the higher risk of recurrence in stage IC and grade 3 immature teratomas.